1997
DOI: 10.1042/bj3210397
|View full text |Cite
|
Sign up to set email alerts
|

The YNT1 gene encoding the nitrate transporter in the yeast Hansenula polymorpha is clustered with genes YNI1 and YNR1 encoding nitrite reductase and nitrate reductase, and its disruption causes inability to grow in nitrate

Abstract: DNA sequencing in the phage lambda JA13 isolated from a lambda EMBL3 Hansenula polymorpha genomic DNA library containing the nitrate reductase-(YNR1) and nitrite reductase-(YNI1) encoding genes revealed an open reading frame (YNT1) of 1524 nucleotides encoding a putative protein of 508 amino acids with great similarity to the nitrate transporters from Aspergillus nidulans and Chlamydomonas reinhardtii. Disruption of the chromosomal YNT1 copy resulted in incapacity to grow in nitrate and a significant reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
60
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 32 publications
(55 reference statements)
2
60
0
1
Order By: Relevance
“…Recently, the Arabidopsis Chl1 gene (the first Nrt1 gene identified) has been reported to produce a system with a dual function, having both high-and low-affinity nitrate transport activity (Wang et al, 1998;Liu et al, 1999). The Nrt2 family encodes high-affinity nitrate transporters (HANTs), and its members have been identified in fungi (Unkles et al, 1991), algae , and yeast (Pérez et al, 1997). Nrt2 genes have also been cloned from plants (Trueman et al, 1996;Quesada et al, 1997;Amarasinghe et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the Arabidopsis Chl1 gene (the first Nrt1 gene identified) has been reported to produce a system with a dual function, having both high-and low-affinity nitrate transport activity (Wang et al, 1998;Liu et al, 1999). The Nrt2 family encodes high-affinity nitrate transporters (HANTs), and its members have been identified in fungi (Unkles et al, 1991), algae , and yeast (Pérez et al, 1997). Nrt2 genes have also been cloned from plants (Trueman et al, 1996;Quesada et al, 1997;Amarasinghe et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The crnA gene has been cloned (9) and belongs to the Major Facilitator superfamily of membrane transporters, being in the same family (nitrate-nitrite porter, NNP) 1 as NarK, the nitrite efflux system from Escherichia coli and the NRT2 high affinity nitrate transporters from algae and higher plants (10). A related nitrate transporter from the yeast Hansenula polymorpha has also been isolated (11). Genes encoding high affinity nitrate transporters from the alga, Chlamydomonas reinhardtii have been isolated and complementation of mutant strains has shown that two genes (Nar2 and either NRT2;1 or NRT2;2) are necessary for a functional nitrate transport system (12).…”
mentioning
confidence: 99%
“…Many studies of the molecular basis of nitrate uptake reveal the existence of two gene families, namely the NRT1 and NRT2 families, which potentially encode for LATS and HATS respectively. NRT2 genes are identified in a variety of organisms including fungi, certain yeasts, green algae, and higher plants ( Unkles et al 1991;Quesada et al 1994;Trueman et al 1996;Pérez et al 1997;Quesada et al 1997;Amarasinghe et al 1998;Zhuo et al, 1999;Araki and Hasegawa 2006;Tsujimoto et al 2007). In most species, NRT2 genes are members of a multigene family: for example, seven Arabidopsis genes (AtNRT2.1-AtNRT2.7) and four rice genes (OsNRT2.1-OsNRT2.4) have been found in their genomes (Orsel et al 2002; Araki and Hasegawa 2007), and at least four NRT2 genes (HvNRT2.1-HvNRT2.4) exist in barley (Vidmar 2000a).…”
mentioning
confidence: 99%